Optimizing the first-line treatment for metastatic colorectal cancer - Cherri, Sara; Oneda, Ester; Zanotti, Laura; Zaniboni, Alberto (Frontiers in Oncology, 2023)
Colorectal cancer represents an important oncological challenge both for its incidence, which makes it an important health problem, and for its biological complexity, which has made clinical results very difficult in terms of outcome for this category of patients. To date these diseases should not be treated as a single entity but it is necessary to distinguish colorectal cancers based on characteristics that nowadays are essential to have greater therapeutic benefits. These include the sideness of the disease, the state of microsatellites, the presence of prognostic and predictive mutations of response to treatments currently available in clinical practice, which are associated with new therapeutic targets. The greatest challenge in the future will be to circumvent the resistance mechanisms that make this disease very difficult to treat with good long-term results by studying effective combination treatments with a good toxicity profile. Once such combinations or targeted treatments are consolidated, it will be desirable to shift the best therapies to the first line treatment to make them immediately accessible to the patient. It will also be essential to refine the selection of patients who can benefit from these treatments.